“It's just a likelihood”: uncertainty as topic and resource in conveying “positive” results in an antenatal screening clinic - Pilnick, Alison; Zayts, Olga (Wiley, 2014)
The recognition of uncertainty as a pivotal issue for the sociology of medicine is longstanding. More recently, the widespread integration of new medical technologies into healthcare has led to a renewed analytic focus on uncertainty. However, there remains little work on the interactional manifestations of uncertainty. This article uses conversation analysis to examine how uncertainty is introduced and used in one specific setting: an antenatal screening clinic in Hong Kong. We focus on women who have received “screen positive” or higher risk results, and reflect on the ways in which uncertainty is an “essential tension” (Mazeland and ten Have 1996) in the activity of conveying these results to them. We conclude that as well as posing potential difficulties for interaction, the uncertainty of test results is also used here as an interactional resource in managing the institutionally defined category of “high risk.”